A new species of Psorodonotus (Orthoptera, Tettigoniidae) from Anatolia, Turkey - Taylan Mehmet Sai̇t; Mol, Abbas; Şi̇ri̇n Deni̇z (Zootaxa, 2014)
Descriptions of a new species of Tettigoniinae; Psorodonotus suphani sp. n. from Turkey were given. The relationships between the new species and closest taxa (morphologically and geographically) were evaluated by using morphological characters. Ultimately, some remarkable points of the distribution pattern of the species were presented.